A study on the factors of work-life balance affecting employees' job performance in Ibu Pejabat Bomba dan Penyelamat Malaysia Negeri Pahang / Nur Aina Mohd Izan - Mohd Izan, Nur Aina (Faculty of Business And Management, 2016)
The purpose of this study is to identify the factors of work-life balance affecting employees' job performance in Ibu Pejabat Bomba dan Penyelamat Malaysia Negeri Pahang. This study investigates three factors of work-life balance which are work-family conflict, work health and flexibility working environment. The questionnaires had been distributed randomly to the employees in Ibu Pejabat Bomba dan Penyelamat Malaysia Negeri Pahang. The respondents for this study were 66 respondents based on Krejcie & Morgan table for a given population. After collected the questionnaires from the respondents, the data had been analyzed by using Statistical Packages for the Social Sciences (SPSS) version 20 to get the results. Based on the findings, most of respondents said that they faced work-life balance problem and the most influential factor was flexibility working environment in Ibu Pejabat Bomba dan Penyelamat Negeri Pahang. The findings also show that employees' job performance is quite good. The researcher suggested that the organization should try to change to the flexible policies to overcome the problem of work-life balance.